2003
DOI: 10.1097/01.asn.0000040596.23073.01
|View full text |Cite|
|
Sign up to set email alerts
|

P53 Mediates the Apoptotic Response to GTP Depletion after Renal Ischemia-Reperfusion

Abstract: Abstract. Ischemic injury to the kidney is characterized in part by nucleotide depletion and tubular cell death in the form of necrosis or apoptosis. GTP depletion was recently identified as an important inducer of apoptosis during chemical anoxia in vitro and ischemic injury in vivo. It has also been shown that GTP salvage with guanosine prevented apoptosis and protected function. This study investigates the role of p53 in mediating the apoptotic response to GTP depletion. Male Sprague-Dawley rats underwent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
166
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(185 citation statements)
references
References 29 publications
15
166
1
3
Order By: Relevance
“…A previous study using a rat model of ischemia-reperfusion injury has shown that p53 protein is an important mediator of renal cell apoptosis whereby inhibition of p53 reduced ischemic injury in rats. 39 In summary, we have identified caspase-6 and -7 but not -3, -8, and -9 as transcriptional targets of p53 in renal tubular cells and the kidney cortex in response to cisplatin-induced AKI. We have characterized the p53-binding sites in the caspase-6 and -7 genes.…”
Section: Discussionmentioning
confidence: 74%
“…A previous study using a rat model of ischemia-reperfusion injury has shown that p53 protein is an important mediator of renal cell apoptosis whereby inhibition of p53 reduced ischemic injury in rats. 39 In summary, we have identified caspase-6 and -7 but not -3, -8, and -9 as transcriptional targets of p53 in renal tubular cells and the kidney cortex in response to cisplatin-induced AKI. We have characterized the p53-binding sites in the caspase-6 and -7 genes.…”
Section: Discussionmentioning
confidence: 74%
“…In mice , morphological changes consistent with ischemic necrosis of renal tubular cells are found after at least 30 minutes of ischemia and after over an hour of reperfusion 49,50 and in rats subjected to ischemia only renal 1 . Common findings relate to renal injury in the ischemic swine model 51 .…”
Section: Resultsmentioning
confidence: 84%
“…In this setting, the depletion of limiting intracellular pools of GTP is an important and specific physiologic inducer of apoptosis (but not of necrosis), and p53 is its critical downstream effector for mediating apoptosis. 13,14 Of note, ischemiainduced stabilization of p53 protein is to a large extent cytoplasmic rather than nuclear and more importantly, strongly colocalizes with mitochondria, as demonstrated in ischemia-reperfusion injured tubules of the outer medulla. This mitochondrial translocation correlates with apoptosis of tubular cells in vivo.…”
mentioning
confidence: 89%
“…Another important pathophysiologic setting in which apoptosis is largely mediated by the mitochondrial p53 program is ischemiareperfusion injury of the kidney leading to acute renal failure, 13 a common clinical problem. Renal ischemia-reperfusion injury, modeled e.g., by transient bilateral renal artery occlusion in rat, is characterized by necrosis and apoptosis of tubular epithelial cells mainly in the outer medulla.…”
mentioning
confidence: 99%
See 1 more Smart Citation